Peran dan Strategi UMKM dalam Mengurangi Tingkat Pengangguran di Indonesia - Reniwati Lubis; Johni Eka Putra; Tri Widayati; Nurjanna Ladjin; Adam Hafidz Al Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the role and strategy of MSMEs in reducing poverty rates in Indonesia. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that MSMEs play an important role in reducing poverty rates in Indonesia. There are several roles of MSMEs in reducing poverty rates, namely poverty reduction and poverty, economic empowerment, local economic growth, increasing income and consumption. In addition, there are several strategies in reducing poverty rates, namely building coworking spaces, collaborating with the Job Training Center (BLK) to provide free job training, providing job vacancy information through social media or job vacancy applications, conducting synergy collaborations with companies, and encouraging productive age people to enter the creative economy world such as social media.